The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Proceedings of the 13th International Conference on Intelligent User Interfaces 2008
DOI: 10.1145/1378773.1378789
|View full text |Cite
|
Sign up to set email alerts
|

Managing a document-based information space

Abstract: We present a novel user interface in the form of a complementary virtual environment for managing personal document archives, i.e., for document filing and retrieval. Our implementation of a spatial medium for document interaction, exploratory search and active navigation plays to the strengths of human visual information processing and further stimulates it.Our system provides a high degree of immersion so that the user readily forgets the artificiality of our environment. Three well-integrated features suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Second-level Examples information retrieval (1884) entity ranking (6) [8], [21], [168] XML retrieval (5) [69], [74], [118] evaluation (35) [52], [162], [290] user activity tracking (2) [18], [27] search (76) [17], [27], [126] recommendation (27) [2], [41], [223] structure analysis (22) [246], [266], [269] query analysis (302) [19], [135], [330] filtering (15) [35], [102], [368] interactive retrieval (12) [138], [142], [284] unstructured information retrieval (107) [90], [204], [359] efficiency and scalability (361) [297], [354], [363] cluster/topic analysis (1624) community discovery (6) [215], [313], [374] text segmentation (26) [66], [174], [326] topic analysis (556) [11], [26], [88] contextual text mining (2) [234],…”
Section: First-levelmentioning
confidence: 99%
“…Second-level Examples information retrieval (1884) entity ranking (6) [8], [21], [168] XML retrieval (5) [69], [74], [118] evaluation (35) [52], [162], [290] user activity tracking (2) [18], [27] search (76) [17], [27], [126] recommendation (27) [2], [41], [223] structure analysis (22) [246], [266], [269] query analysis (302) [19], [135], [330] filtering (15) [35], [102], [368] interactive retrieval (12) [138], [142], [284] unstructured information retrieval (107) [90], [204], [359] efficiency and scalability (361) [297], [354], [363] cluster/topic analysis (1624) community discovery (6) [215], [313], [374] text segmentation (26) [66], [174], [326] topic analysis (556) [11], [26], [88] contextual text mining (2) [234],…”
Section: First-levelmentioning
confidence: 99%
“…Evaluating these techniques indicated that they are fun and enable an efficient interaction. Further, Deller et al [20] introduced interaction techniques for managing 2D documents within a virtual work desk.…”
Section: Working With 2d Content In 3dmentioning
confidence: 99%
“…For example, they present an array of layered screen arranged around the user that expands the users small portable display and an application that visualizes 3D data on top of a touchscreen device (Figure 3). Dengel et al [21] and Deller [20] presented applications for working with documents on a stereoscopic display There are also commercially available solutions that support knowledge work in virtual reality, such as Oculus Infinite Office [1] where the user can open virtual browser windows and interact with them using a controller, gestures or a physical keyboard which is included in the virtual environment as a 3D model and a video pass-through visualization of the hands while typing. An example for AR would be spatial.io [2] which allows collaborative meetings by representing remote coworkers as avatars…”
Section: Applicationsmentioning
confidence: 99%
“…Visualization of personal document archives has also been discussed (e.g. [8]). Most of them give specific meanings to axes of 2D or 3D space.…”
Section: Visualization Of Other Kinds Of Large Collectionmentioning
confidence: 99%